Aplicación del Flipped Classroom para el logro del aprendizaje significativo - Vásquez-Vásquez , Alvaro Wladimir; Zuloaga-Cachay, José Fortunato; Díaz-Paredes , Manuel Antonio; Lau-Hoyos , Edgar Mitchel; Chayán-Coloma , Alejandro; Tineo-Huancas, Rodolfo Pastor (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The objective of the research is to demonstrate that the application of the Flipped Classroom improves the level of achievement of meaningful learning in university students. For data collection in the control and experimental groups, two instruments were applied: the pre-test and the post-test. Concluded with the application of the workshops based on the FC methodology, in the post test it was observed that in the control group, 26 students obtained a passing grade and 11 failed, while in the experimental group, 38 students, according to the evaluation criteria, all achieved a passing grade.